Early post-Humanitarian Device Exemption experience with the Neuroform Atlas stent. (12th April 2019) - Tsai, Jenny P; Hardman, Julian; Moore, Nina Z; Hussain, M Shazam; Bain, Mark D; Rasmussen, Peter A; Masaryk, Thomas J; Elgabaly, Mohammed H; Sheikhi, Lila; Toth, Gabor
Abstract : Introduction: The low-profile Neuroform Atlas stent received FDA Humanitarian Device Exemption status (HDE) in January 2018 for stent-assisted coil embolization of wide-necked saccular aneurysms. We review and report our results with the Atlas stent in our institution within the first year after its HDE approval. Methods: Our retrospective chart review identified patients treated with the Atlas stent. We analyzed the patient demographics, aneurysm characteristics, stent parameters and configuration, complications, angiographic, and clinical outcomes at discharge. Results: From January to December 2018, 76 Atlas stents were deployed in 58 patients (average 1.3 stents/patient). Median patient age was 63.5 (IQR 56–71) years. Fifty-six (96.6%) patients had elective embolization of unruptured aneurysms, while two (3.4%) patients underwent embolization of a ruptured aneurysm within 2 weeks of subarachnoid hemorrhage. Forty (69.0%) patients were treated with a single stent, 15 (25.9%) with a Y-stent, and three (5.2%) with X-stent configuration. All stent deployments were technically successful. Most stents (82.9%) were the smallest 3 mm diameter devices. Procedural complications included transient stent-associated thrombosis in three (5.2%) patients and aneurysm rupture in one (1.7%). None had distal embolization, associated cerebral infarction, or permanent neurological deficits. Immediate Raymond–Roy 1 occlusion was achieved in 41 (70.7%) patients. Median hospital length of stay for elective aneurysm embolization was 1 day. Excellent outcomes with median National Institute of Health Stroke Scale score 0 (IQR 0–0) and modified Rankin Score 0 (IQR 0–1) were seen for elective patients at discharge. Conclusion: The Neuroform Atlas stent provided a reliable technical and safety profile for the treatment of intracranial wide-neck aneurysms. Further experience is needed to determine long-term durability and safety of this device.